Developing a critically inclusive study of religion - Meyer, Gaelin (Department of Religious Studies, 2025)
The scientiﬁc, or secular, study of religion is a relatively new endeavour, and has faced multiple obstacles over the course of its development. The primary challenge has consisted of the need to distinguish the secular study of religion from the theological study of religion. The commitment to exclusive humanism has played a foundational role in this process. This form of humanism developed during Europe's colonial era and helps to cement the modern secular worldview. That said, there are critical material scholars who attempt to move beyond the strictures of their colonial inheritance. New models for examining the materiality of religion have followed the integration of new-materialist theory into critical religion research. Along with new-material approaches, the way opens to posthuman studies of religion. This allows scholars to critically engage with the outdated and racialised categories that emerged in 19th century humanist discourse. However, the domain of posthuman studies is not altogether free of colonial baggage, and this shows in the lack of black and indigenous voices in the ﬁeld. Both the material study of religion, and the posthuman study of religion lack a coherent engagement with indigenous worlds and therefore remain within modern colonial boundaries. These exclusions correlate with the unexamined commitment to secular rhetoric within the modern academy. As a modern construct, the secular domain makes absent the world-making practices of indigenous collectives and renders them invisible within critical discourse. To remedy this, I point to the work of nonmodern scholars, who present alternate ontologies and epistemologies that require attention should the critical study of religion wish to develop into an inclusive domain of academic enquiry.